2022
DOI: 10.1002/adhm.202201651
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Corrole/Chitosan Photothermal Nanoparticles for Accelerating Infected Diabetic Wound Healing

Abstract: Microvascular dysfunction caused by hyperglycemia leads to slow healing of diabetic wounds and significantly increases the risk of bacterial infection. The misuse of antibiotics can also lead to bacterial resistance, making the management of diabetic wounds more challenging. Thus, developing new antibacterial agents or strategies to overcome antibiotic resistance is highly pursued. Herein, novel supramolecular photothermal nanoparticles (MCC/CS NPs), assembled from mono-carboxyl corrole (MCC) and chitosan via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…In contrast, both mature epidermal layer (red arrow) and skin appendages (blue arrow) formed in the AuPt/GOx gel + glucose + NIR group, indicating the elevated wound healing process. Collagen plays a crucial role in tissue reconstruction, which can be employed as a marker for evaluating wound healing . Thus, Masson staining was carried out to assess collagen fiber deposition (stained as blue).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, both mature epidermal layer (red arrow) and skin appendages (blue arrow) formed in the AuPt/GOx gel + glucose + NIR group, indicating the elevated wound healing process. Collagen plays a crucial role in tissue reconstruction, which can be employed as a marker for evaluating wound healing . Thus, Masson staining was carried out to assess collagen fiber deposition (stained as blue).…”
Section: Resultsmentioning
confidence: 99%
“…Collagen plays a crucial role in tissue reconstruction, which can be employed as a marker for evaluating wound healing. 34 Thus, Masson staining was carried out to assess collagen fiber deposition (stained as blue). It was found that the blue color in the AuPt/GOx gel + glucose + NIR group is the darkest, revealing the maximal amount of collagen fibers.…”
Section: In Vivo Wound Healing Evaluationmentioning
confidence: 99%
“…223 Therefore, researchers focus on new antibacterial strategies applied in developing antibacterial hydrogels to combat multiple drug resistant bacterial infections. 84,224,225 This section will introduce the latest research progress in various supramolecular hydrogels used to achieve antibacterial function in the field of wound healing, including the introduction of natural polymers and metal ions/nanoparticles, cation antibacterial strategies, photothermal antibacterial therapy 226 and the combination of these antibacterial strategies to enhance antibacterial function. 8 Some natural polymers with biocompatibility are widely used in the preparation of inherently antibacterial supramolecular hydrogels because of their universal or conditional antibacterial properties.…”
Section: Application Of Supramolecular Hydrogels In Wound Repairmentioning
confidence: 99%
“…[1,2] Delivering large populations of photothermally active nanoagents to the diseased site can kill solid tumors and bacteria in infected diabetic ulcers, via noxious heat. [3][4][5] Moreover, regulating the heat dose to mild levels has been shown to significantly enhance wound healing. [6,7] Furthermore, neuromodulation via photothermal heating was recently proposed as a therapeutic strategy to prevent ventricular arrythmias and to treat depression.…”
Section: Introductionmentioning
confidence: 99%